2009
DOI: 10.3831/kpi.2009.12.1.053
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical study on the Traditional Korean Medicine treatment of Amyotrophic lateral sclerosis

Abstract: ALS 3-5 symptomatic treatment supprotive 53 A pilot clinical study on the Traditional Korean Medicine treatment of Amyotrophic lateral sclerosis Kim Sung-chul, Na Won-min, Lim Na-ra, Lee Do-sang, Jang Eun-ha*, Song Bong-keun**

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…All the studies were conducted in China and South Korea. There were 39 [ 4 , 8 , 13 , 18 , 19 , 24 – 26 , 29 – 34 , 39 – 41 , 44 – 58 , 60 – 65 , 68 ] and 20 [ 7 , 14 – 17 , 20 – 23 , 27 , 28 , 35 – 38 , 42 , 43 , 59 , 66 , 67 ] studies conducted in China and South Korea, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were conducted in China and South Korea. There were 39 [ 4 , 8 , 13 , 18 , 19 , 24 – 26 , 29 – 34 , 39 – 41 , 44 – 58 , 60 – 65 , 68 ] and 20 [ 7 , 14 – 17 , 20 – 23 , 27 , 28 , 35 – 38 , 42 , 43 , 59 , 66 , 67 ] studies conducted in China and South Korea, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown that Mecasin, a herbal extract, has neuro-protective and anti-neuroinflammatory effects, and its safety has been proven in both in vitro and in vivo trials [ 8 14 ]; it has been shown to reduce the progression of ALS in Korean Medicine Clinics [ 6 , 7 ]. No previous randomized controlled trial has examined the effects of Mecasin for the treatment of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…However, it severely decreased to 21.33 ± 9.93 at 8 months from discharge [ 6 ]. Another study showed that 30 days of the combined therapy led to a K-ALSFRS-R score increase from 28.42 ± 7.83 to 29.08 ± 7.99 [ 7 ]. Mecasin, also known as KCHO-1, a herbal extract from modified jakyakgamchobuja-tang , has shown neuro-protective and anti-neuroinflammatory effects and safety in both in vitro and in vivo trials [ 8 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…한의학적 치료 증례보고 20 Ecklonia Cava Extract × 32,34,36,40) , 흉민과 단기 30,32,33) , 기침과 가래 26,32) , 발한 30) , 상열감 30,31) , 식 욕부진 42) , 무력감 37) 의 호전도 역시 보고되었다. …”
Section: )Alsssunclassified